Career Development and Discipline as Key Drivers of Employee Performance: Insights from a Banking Firm in Bandung - Rio Valetehan; Adhie Nurhadian; Nenny Rinawati; Vicky Achmad Zulfikar (P3M, STIE Pasundan, Bandung, Indonesia., 2026)
This study addresses the critical issue of employee performance at a prominent bank in Bandung. Employee performance directly impacts organizational success, yet many financial institutions struggle with engagement and productivity levels. Using a survey approach, this research gathers data from employees to explore the relationships between career development, discipline, and performance outcomes. The analysis employs path analysis to identify direct and indirect effects among the variables. The findings reveal that both career development and discipline significantly influence employee performance, with career development emerging as a key motivator that enhances engagement. This research contributes novel insights by highlighting how these factors interconnect within the banking sector, emphasizing the importance of a structured approach to employee growth and compliance. The implications suggest that banks should focus on fostering career development and maintaining a disciplined work environment to drive higher employee performance, ultimately improving the bank’s overall effectiveness and competitive edge in the industry.